Produção por cultivo submerso e parcial caracterização de uma nova lipase do fungo endofítico Preussia africana - Oliveira, Gustavo Francisco De (2021)
Endophytes are microorganisms that live inside vegetable tissues for at least a fraction of their life cycle producing a wide range of enzymes and secondary metabolites that can be used by the host plant, providing a higher vegetable adaptability. The goal of the present work has been to study the production of a new extracellular lipase produced by the endophytic fungus Preussia africana (P. africana), isolated from Ipê- roxo, at the South of Minas Gerais region. The assays were conducted to evaluate the influence of different inductor oils (sunflower, cottonseed, corn, palm kernel, canola and linseed) and the Carbon/Nitrogen ratio (C/N of 11,73, 8,63, 7,05) in the production by submerged culture, aiming the majority production of one single extracellular lipase. The results showed that the majority production of one single lipase of 14,5 kDa was achieved after 48 h of growth, at 30 oC and 250 rpm, when sunflower oil and a C/N ratio of 8,63 were used in the culture medium. Still, the produced lipase was characterized as to optimum pH and temperature, using a factorial design for two independent variables. Only pH was statistically significant at 5% of significance, and the best activity values were obtained for pH values between 5,0 to 7,0 (about 28 U/mL). The studied temperature interval (from 20 to 54 oC) did not influence statistically the produced lipase activity, showing that its catalytic activity is unaffected for a wide range of temperature.